Crystal structure of the read‐through domain from bacteriophage Qβ A1 protein - Rumnieks, Janis; Tars, Kaspars (Protein science, 2011)
Bacteriophage Qβ is a small RNA virus that infects Escherichia coli. The virus particle contains a few copies of the minor coat protein A1, a C‐terminally prolonged version of the coat protein, which is formed when ribosomes occasionally read‐through the leaky stop codon of the coat protein. The crystal structure of the read‐through domain from bacteriophage Qβ A1 protein was determined at a resolution of 1.8 Å. The domain consists of a heavily deformed five‐stranded β‐barrel on one side of the protein and a β‐hairpin and a three‐stranded β‐sheet on the other. Several short helices and well‐ordered loops are also present throughout the protein. The N‐terminal part of the read‐through domain contains a prominent polyproline type II helix. The overall fold of the domain is not similar to any published structure in the Protein Data Bank. PDB Code(s): 3RLC, 3RLK